2023
DOI: 10.1037/rel0000455
|View full text |Cite
|
Sign up to set email alerts
|

Conflict between religious/spiritual and LGB identities in Portugal: How is it related to coming out experiences, LGB identity dimensions and well-being?

Abstract: Even though Lesbian, Gay, and Bisexual (LGB) individuals are usually less religious than the general population, religion and/or spirituality are still a part of many LGB people's lives. This article focused on investigating the relation between the conflict between religious/spiritual and LGB identities and subjective well-being, dimensions of LGB identity and outness, in a Portuguese sample. The participants were 126LGB people, with 80 of them being female, from a mostly Catholic context in Southern Europe-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Identity conflict itself is not an aspect of religiosity but refers to the tension that many LGBTQ individuals feel between their religious and sexual-gender identities. Studies that examine the role of identity centrality and integration with other aspects of LGBTQ well-being indicate that conflict between religious and sexual-gender identities almost universally leads to deleterious outcomes (Beagan & Hattie, 2015; Dahl & Galliher, 2012; Fernandes et al, 2023; Sherry et al, 2010). Such conflict is central to both minority stress theory and Cass’ identity development model.…”
Section: Discussionmentioning
confidence: 99%
“…Identity conflict itself is not an aspect of religiosity but refers to the tension that many LGBTQ individuals feel between their religious and sexual-gender identities. Studies that examine the role of identity centrality and integration with other aspects of LGBTQ well-being indicate that conflict between religious and sexual-gender identities almost universally leads to deleterious outcomes (Beagan & Hattie, 2015; Dahl & Galliher, 2012; Fernandes et al, 2023; Sherry et al, 2010). Such conflict is central to both minority stress theory and Cass’ identity development model.…”
Section: Discussionmentioning
confidence: 99%
“…The researchers validated the identity centrality subscale in two different samples of adult SM undergraduate students, and found that concealment of sexual identity predicts lower identity centrality (Mohr & Kendra, 2011). The subscale has been replicated in a handful of studies with mixed findings regarding its relation to other domains of well-being (Dunn & Szymanski, 2018; Fernandes et al, 2023; Jennings & Sprankle, 2023). A systematic meta-analysis of identity centrality found that identity centrality was associated with higher levels of prejudice and discrimination centrality (Hinton et al, 2022).…”
Section: Sm Individuals Coming Out and The Life Coursementioning
confidence: 99%